Extraction by biocatalytic action and quantification of lutein from tomato of tree (Cyphomandra betacea) - Córdova, Javier S. (2014)
The amount of oleoresin was determined and the bioactive components were quantified by high efficiency liquid chromatograph (HPLC) obtaining, in the chromatograms, lutein, beta-carotene and licopene in large quantities. After determination of fruit maturity index, the fruits were conditioning –it was 4,71–; then were dehydrated at 40°C for 96 hours on a tray dryer, and were ground and sieved by) a mesh with diameter smaller than 425 μm. Subsequently, the cell walls were hydrolyzed to extract lutein from dry tissue using a cellulose enzyme complex. Following leaching was performed using a mixture of hexane, ethanol, acetone and toluene in a ratio of 10:6:7: 7 (v/v/v/v) at a temperature of 35°C for a time of 3 hours. The third treatment gave better results in the extraction of lutein, this was performed at 30°C for 4 hours and substrate:enzyme ratio 1:16. A yield of 98,30 mg lutein / 100g of dry matter was obtained. The identified chromatographic peaks of lutein, β-carotene and lycopene, had characteristic spectra with wavelengths of maximum absorption of 446, 452 and 471 ŋm, respectively.